ChemInform Abstract: Alkoxylation Reactions of Aryl Halides Catalyzed by Magnetic Copper Ferrite. Issue 34 (1st August 2013) - Yang, Shuliang; Xie, Wenbing; Zhou, Hua; Wu, Cunqi; Yang, Yanqin; Niu, Jiajia; Yang, Wei; Xu, Jingwei
Abstract An efficient C—O and C—S coupling reaction between aryl halides and unactivated alkyl alcohols and thiols is described.